Apoptosis, Pyroptosis, and Ferroptosis Conspiringly Induce Immunosuppressive Hepatocellular Carcinoma Microenvironment and γδ T-Cell Imbalance - Hu, Yi; Chen, Dan; Hong, Minjing; Liu, Jing; Li, Yijia; Hao, Jianlei; Lu, Ligong; Yin, Zhinan; Wu, Yangzhe (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is highly malignant and prone to metastasize due to the heterogeneous and immunosuppressive tumour microenvironment (TME). Programmed cell deaths (PCDs) including apoptosis, ferroptosis, and pyroptosis routinely occur in the HCC TME and participate in tumorigenesis. However, how apoptosis, ferroptosis, and pyroptosis involve in constructions of the immunosuppressive TME and their underlying crosstalk remain to be further unveiled. In this work, we deciphered the immunosuppressive landscape of HCC TME, which demonstrated high expressions of inhibitory checkpoint molecules and infiltration of pro-tumour immune cells but low infiltration of anti-tumour effector immune cells. Further investigations unequivocally revealed marker genes of apoptosis, ferroptosis, and pyroptosis are closely correlated with expressions and infiltrations of inhibitory checkpoint molecules and immune cells, respectively, and that higher ‘-optosis’ links to poorer patient prognosis. Notably, such three types of ‘-optosis’ interact with each other at both the gene and protein levels, suggesting they conspiringly induce the establishment of the immunosuppressive HCC TME. Interestingly, examinations of circulating γδ T cells in HCC patients revealed a noticeable dysfunction phenotype. The strikingly elevated ratio of the Vδ1+ verses the Vδ2+ subset suggested the Vδ1+/ Vδ2+ ratio would be a potential biomarker for diagnosis and prognosis in HCC patients. Altogether, this work thoroughly decrypted the underlying correlations between apoptosis, ferroptosis, and pyroptosis and the formation of immunosuppressive HCC TME, meanwhile, indicated allogeneic Vδ2+ γδ T cells transfer would be a promising adjuvant strategy for renormalizing circulating-γδ T cell and thus achieve sound clinical efficacy against HCC.